WAYS TO IMPROVE THE MECHANISM OF FINANCING AGRICULTURAL PRODUCTS EXPORT (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
This article examines the current state of financing mechanisms for agricultural product exports and proposes ways to enhance their effectiveness. Through a comprehensive literature review and analysis, the study identifies key challenges in export financing and presents strategies for improvement. The research emphasizes the importance of innovative financial instruments, government support programs, and international cooperation in boosting agricultural exports.